Vývoj průmyslového lepidla pro ukládání nenasákavých prvků - Bergerová, Kamila (Vysoké učení technické v Brně. Fakulta stavební, 2017)
Tato práce se zabývá vývojem průmyslového lepidla pro ukládání nenasákavých prvků v prostředích vystavených působení agresivních chemikálií a vysokých teplot. Teoretická část je převážně zaměřena na shrnutí poznatků o lepicích hmotách. Práce rovněž zahrnuje popis lepených prvků, věnuje se teorii lepení a představuje použité materiály. Práce si klade za cíl předložit návrh materiálové složení nového průmyslového lepidla na silikátové i polymerní bázi. Zároveň práce zkoumá možnosti využití průmyslového odpadu jako druhotných surovin. Závěr se věnuje laboratornímu testování nově vyvinutých hmot, shrnutí a diskuzi zjištěných výsledků.

The thesis deals with the development of industrial adhesive material for deposition of nonabsorbent components in environments exposed to aggressive chemicals and high temperatures. The theoretical part is mainly focused on summarizing knowledge about adhesive materials. The study also includes description of bonded components, describes theory of adhesion and introduces the used materials. The primary aim of this work is to present new design of material composition of a new adhesive of polymer and silicate base material. The work also investigates the possibility of using the industrial waste in the form of secondary raw material. The final part is dedicated to laboratory testing of new developed materials, summarization and discussion of the obtained results.
Development of industrial adhesive material for deposition of nonabsorbent components
Keywords: lepicí hmoty; druhotné suroviny; tepelná odolnost; chemická odolnost; nenasákavé prvky; adhesive materials; secondary raw materials; heat resistance; chemical resistance; nonabsorbent components